2005
DOI: 10.1086/426453
|View full text |Cite
|
Sign up to set email alerts
|

16α‐Bromoepiandrosterone Restores T Helper Cell Type 1 Activity and Accelerates Chemotherapy‐Induced Bacterial Clearance in a Model of Progressive Pulmonary Tuberculosis

Abstract: BALB/c mice with pulmonary tuberculosis develop a T helper cell type 1 response that peaks at 3 weeks, temporarily controlling bacterial growth. Then bacterial proliferation recommences, accompanied by increasing interleukin (IL)-4 levels and decreasing interferon (IFN)-gamma, tumor necrosis factor (TNF)-alpha, and inducible nitric oxide synthase (iNOS) levels. These changes mimic those in the human disease. In a previous study, administration of dehydroepiandrosterone (DHEA) beginning on day 60 after infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
42
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 34 publications
3
42
0
Order By: Relevance
“…28 In this context, natural dietary components are gaining immense importance as potent immunomodulators with multifarious roles and targets, as they not only boost the immune system to produce microbicidal molecules such as NO and ROS, but also modulate the Th1/Th2 cytokine balance in favor of the host. 30,31 Although the mouse model of VL suffers from several limitations as it differs from symptomatic human VL, it remains a good experimental model for early infection of L. donovani. The present study has exploited the use of a mouse model of VL up to 6 weeks, a time frame for which it closely mimics human VL, and can be used for further development of fucoidan as a therapeutic target against L. donovani.…”
Section: Discussionmentioning
confidence: 99%
“…28 In this context, natural dietary components are gaining immense importance as potent immunomodulators with multifarious roles and targets, as they not only boost the immune system to produce microbicidal molecules such as NO and ROS, but also modulate the Th1/Th2 cytokine balance in favor of the host. 30,31 Although the mouse model of VL suffers from several limitations as it differs from symptomatic human VL, it remains a good experimental model for early infection of L. donovani. The present study has exploited the use of a mouse model of VL up to 6 weeks, a time frame for which it closely mimics human VL, and can be used for further development of fucoidan as a therapeutic target against L. donovani.…”
Section: Discussionmentioning
confidence: 99%
“…Among hormonal effects on the immune response, glucocorticoids can promote a Th2 cytokine acquisition profile [14], facilitating Th2 activities, whereas its natural antagonist dehydroepiandrosterone (DHEA) is able to favor Th1 cytokine production and interfere with Th2 cytokine synthesis [15]. In fact, the synthetic DHEA derivative, 16 α-bromoepiandrosterone, exerts beneficial effects in clinical and experimental TB and in HIV patients [16][17][18]. We have previously demonstrated that in vitro treatment of PBMCs from HIV-TB patients with DHEA increased Mtb-specific IFN-γ responses and decreased FoxP3 expression in regulatory T cells, thus inducing a bias toward a protective antitubercular immune response [19].…”
mentioning
confidence: 99%
“…HE2000 is clinically active in clearing malarial parasites in patients with uncomplicated malaria (7). It is also active against feline immunodeficiency virus, rodent tuberculosis, and rodent malaria (1,6,8,12).…”
mentioning
confidence: 99%